Bees in the City - Falencka-Jabłońska, Malgorzata (Studia Ecologiae et Bioethicae, 2022)
For many years, the need to increase food production, both globally and locally, has been directly related to agriculture intensification. The need to systematically increase the doses of both artificial fertilizers and chemical plant protection products increases the threat to the components of the natural environment. This condition is hazardous and has far-reaching consequences for pollinating insects, especially bees. Consequently, the number of these is decreasing, and their susceptibility to numerous diseases is increasing significantly. The research results indicate that they pollinate 80% of plants on our planet, especially such essential utility species as vegetables and fruits. To counteract and limit the harmful effects of chemical plant protection products on the life of these insects, in 2018, the European Union issued a ban on the use of the most potent pesticides, i.e., neonicotinoids, and glyphosate, the main ingredient of Roundup. One method of helping these insects are urban apiaries which can help in reducing their exposure to diseases and, consequently, their mortality. The practice of establishing beehives in the cities of Europe and other countries around the world has been observed for several decades now, and in Poland it has a tradition of several years. The number of such apiaries is increasing, as the urban landscape provides a rich and varied diet for bees.